2015
DOI: 10.1177/0885328215569091
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced osteogenesis on titanium implants by UVB photofunctionalization of hydrothermally grown TiO2 coatings

Abstract: Even though Ti-based implants are the most used materials for hard tissue replacement, they may present lack of osseointegration on the long term, due to their inertness. Hydrothermal treatment (HT) is a useful technique for the synthesis of firmly attached, highly crystalline coatings made of anatase titanium dioxide (TiO 2 ), providing favorable nanoroughness and higher exposed surface area, as well as greater hydrophilicity, compared to the native amorphous oxide on pristine titanium. The hydrophilicity dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Sr‐incorporated surfaces with such nanoparticle coatings indeed showed super‐hydrophilic properties in our study, which was in accordance with the above reports. It is believed that super‐hydrophilic surfaces would not only enhance cell attachment, spreading, settling and subsequent proliferation and differentiation in vitro (Lorenzetti et al, ; Ogawa et al, ) but also be good for early osseointegration with dental implants in vivo compared with hydrophobic surfaces (Hicklin et al, ; Minamikawa et al, ; Vasak et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Sr‐incorporated surfaces with such nanoparticle coatings indeed showed super‐hydrophilic properties in our study, which was in accordance with the above reports. It is believed that super‐hydrophilic surfaces would not only enhance cell attachment, spreading, settling and subsequent proliferation and differentiation in vitro (Lorenzetti et al, ; Ogawa et al, ) but also be good for early osseointegration with dental implants in vivo compared with hydrophobic surfaces (Hicklin et al, ; Minamikawa et al, ; Vasak et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the photocatalytic nature of the nanocrystalline anatase coatings improved the bioperformances of the titanium substrate upon photoinduction by UV light. The photoactivated surfaces reduced the adsorption of inflammation-promoter plasma proteins and increased the bioactivity and osteogenesis due to the positive interaction of human mesenchymal stem cells with the HT coatings …”
Section: Introductionmentioning
confidence: 99%
“…The photoactivated surfaces reduced the adsorption of inflammation-promoter plasma proteins 20 and increased the bioactivity and osteogenesis due to the positive interaction of human mesenchymal stem cells with the HT coatings. 21 An alternative approach introduces functionalities onto the Ti-based implant surfaces, which can reduce the biocontamination level, improve the ability to self-clean, or both. The photoinduced phenomena occurring on TiO 2 surfaces upon UV irradiation are currently under study by several research groups who have reported the potential bactericidal effect of titania coatings under UV light (photokilling).…”
Section: ■ Introductionmentioning
confidence: 99%
“…This layer minimizes both metallic ion release from the implant to the surrounding tissues10 and adverse body reactions11, and it has been considered to be of great importance for successful osseointegration. The properties of this surface oxide layer can markedly influence the biocompatibility of titanium1213. Thus, various surface oxidation methods, such as electrochemical treatment (anodic oxidation), chemical (acid and alkali) treatment, plasma spray deposition, sol-gel formation, ion implantation, and thermal oxidation, have been employed to develop a functional implant surface by changing the surface properties of the native passive layer to improve osseointegration141516171819.…”
mentioning
confidence: 99%